Association of Serum Osteoprotegerin Level With Myocardial Injury and Cardiovascular Calcification in Chronic Kidney Disease Patients - Okasha, Kamal M.; Aboufreikha, Mohamed Hussein; Elrefaey, Waleed; Ashmawy, Medhat M.; Mourad, Heba; Elsebaey, Mohamed A.; Elnaggar, Mohammed H.; Mashaal, Raghda Gabr; Metwally, Sama; Mashal, Shaimaa Samir Amin; Shalaby, Neveen A.; Elhoseny, Shireen Ali; et al. (Frontiers in Medicine, 2022)
Background Chronic kidney disease has emerged as a significant independent risk factor for cardiovascular disease. Cardiovascular calcification is an active process involving a complex interaction of inducers and inhibitors. High sensitivity cardiac troponin T assay detects troponin T with higher sensitivity and precision at an earlier point of time than the conventional assays, and is associated with poor outcomes. Serum osteoprotegerin is classed as an inhibitory factor for cardiovascular calcification. It is involved in the pathological processes of vascular damage and linked to the excess cardiovascular morbidity. The aim of the present study was to evaluate the extent of cardiovascular calcification and serum high sensitivity cardiac troponin T level, and their association with serum osteoprotegerin level in patients with chronic kidney disease stages 3–5. Methods 90 chronic kidney disease patients were enrolled in this study, and they were divided into two groups: group (1) included 45 non-dialysis-dependent chronic kidney disease patients (stages 3–5) and group (2) included 45 chronic hemodialysis patients. Each group further subdivided according to the presence of cardiovascular calcification into subgroup A and B. Vascular calcifications were assessed by lateral lumbar, pelvis and hands X-ray radiographs. Valvular calcification was assessed by echocardiography. Serum cardiac troponin T was measured by high sensitivity assay and serum osteoprotegerin was measured by ELISA. Results Cardiovascular calcification distribution was 22.2% in group (1) and 33.3% in group (2). Serum osteoprotegerin and troponin T in calcification groups (1A and 2A) were significantly higher than non-calcification groups (1B and 2B; P < 0.001). Osteoprotegerin correlated positively with high sensitivity cardiac troponin T (rs = 0.72, P < 0.001). cardiovascular calcification correlated positively with osteoprotegerin, troponin T, and phosphorus. osteoprotegerin and phosphorus were significant independent predictors of cardiovascular calcification at cut-off values ≥4.6 ng/L and ≥6.95 mg/dl, respectively (P < 0.001). Serum phosphorus and creatinine were independent predictors of osteoprotegerin (P < 0.001 and 0.048, respectively). Conclusion Osteoprotegerin is strongly associated with cardiovascular calcification and high sensitivity cardiac troponin T. In addition, there is a positive association between calcification and troponin T. This suggests a role for osteoprotegerin in the pathogenesis and risk stratification of cardiovascular calcification and myocardial injury in chronic kidney disease patients with a potential role as a therapeutic target.